Tax avoidance motives in property and real estate firms - Cintia Aulia Ramadanti; Donny Maha Putra (Jurnal Akuntansi Aktual, 2022)
AbstractThe purpose of this study is to examine and determine the impact of CSR, capital intensity, and corporate risk on tax avoidance in property and real estate sector firms listed on the Indonesia Stock Exchange from 2016 to 2019. This quantitative study utilized secondary data from 101 sample companies collected purposively. To test the hypotheses, multiple linear regression was employed. The findings showed that CSR had no effect on tax avoidance. In contrast, capital intensity had a negative impact on tax avoidance, whereas corporate risk had a positive impact. Thus, it is implied that property and real estate companies do not use their fixed assets to take advantage of depreciation to avoid taxes that can harm the government; on the contrary, companies have fixed assets to run their operations.Keywords: Tax Avoidance; Capital Intensity; Corporate Risk; Corporate Social ResponsibilityAbstrakTujuan penelitian ini adalah untuk meneliti pengaruh CSR, intensitas modal, dan resiko perusahaan terhadap penghindaran pajak di perusahaan sector property dan real estate yang terdaftar di Bursa Efek Indonesia mulai tahun 2016 sampai dengan 2019. Penelitian kuantitatif ini menggunakan data sekunder dari 101 data perusahaan. Regresi linear berganda digunakan dalam penelitian ini untuk menguji hipotesis. Hasil penelitian menunjukkan bahwa CSR tidak memiliki pengaruh terhadap penghindaran pajak. Namun, intensitas modal memiliki pengaruh negative terhadap penghidaran pajak, sedangkan resiko perusahaan memiliki pengaruh positif. Hal itu berarti perusahaan property dan real estate tidak menggunakan asset tetap perusahaan sehubungan dengan depresiasi untuk menghindari pajak yang dapat merugikan pemerintah. Sebaliknya, perusahaan menggunakan asset tetap untuk menjalankan kegiatan operasional perusahaan.Kata Kunci: Penghindaran Pajak; Intesitas Modal; Risiko Perusahaan; Corporate Social Responsibility